Mechanism of Reversible Self‐Association of a Monoclonal Antibody: Role of Electrostatic and Hydrophobic Interactions. Issue 2 (18th November 2014) - Esfandiary, Reza; Parupudi, Arun; Casas‐Finet, Jose; Gadre, Dhanesh; Sathish, Hasige
<x xml:space="preserve">Abstract</x> Reversible self‐association of protein therapeutics, the phenomenon of formation of native reversible oligomeric species as a result of noncovalent intermolecular interactions, can add additional manufacturing, stability, delivery, and safety complexities in biopharmaceutical development. Its early detection, characterization, and mitigation can therefore contribute to the success of drug development. A variety of structural and environmental factors can contribute to the modulation of self‐association with mechanisms still elusive in some cases due to the inherent structural complexity of proteins. By combining the capabilities of dynamic and static light scattering techniques, the modulatory effects of a variety of solution conditions on a model IgG1's (mAbA) intermolecular interactions have been utilized to derive mechanism of its self‐association at relatively low‐protein concentration. The analysis of the effect of pH, buffer type, Hofmeister salts, and aromatic amino acids utilizing light scattering supported a combined role of hydrophobic and electrostatic interactions in mAbA self‐association. Fitting of the data into the equilibrium models obtained from the multiangle static light scattering provided the enthalpic and entropic contributions of self‐association, highlighting the more dominant effect of electrostatic interactions. In addition, studies of the Fab and Fc fragments of mAbA suggested the key role of the former in observed self‐association. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:577–586, 2015